Clinical Efficiency of Non-Contact Infrared Thermometer over Axillary Digital Thermometer and Mercury in Glass Thermometer with Paracetamol - Tuladhar, Lujaw Ratna; Shrestha, S; Ghimire, N; Acharya, N; Tamrakar, ET (Nepal Medical College Journal, 2021)
Fever is defined as rise in normal body temperature above 98.6°F. Clinical thermometer is a medical instrument for measuring human body temperature. The traditionally used mercury in glass thermometer was replaced by digital thermometer due to mercury toxicity. Non-contact infra-red thermometer is a non-invasive thermometer used for un-cooperative pediatric patients. The objective of this study is to determine the clinical efficiency of non-contact infrared thermometer over axillary digital thermometer and mercury in glass thermometer over a range of body temperature by using paracetamol in febrile patients. This descriptive hospital based cross sectional study was conducted from 5th December 2019 till 23rd August 2020 after ethical approval from Institutional Review Committee of Nepal Medical College and Teaching Hospital. Mercury in glass thermometer, axillary digital thermometer and non-contact infrared thermometer were used to measure body temperature in febrile patient. Body temperature was re-measured one hour after administration of paracetamol. Data was entered and analyzed with statistical package for social sciences version 16. Axillary digital thermometer has high predictability in the upper body temperature range (in febrile state) but its predictability is low in lower body temperature range (our normal body temperature). Non-contact infrared thermometer in comparison with axillary digital thermometer has lower predictability in both upper and lower body temperature range. Clinical efficiency of non-contact infrared thermometer is less than that of axillary digital thermometer and mercury in glass thermometer in febrile patients.